Energy threshold calibration of the GAPS experiment Si(Li) tracker readout electronics - Ghislotti L.; Boezio M.; Fabris L.; Lazzaroni P.; Manghisoni M.; Ratti L.; Re V.; Riceputi E.; Zampa G. (2024)
GAPS (General AntiParticle Spectrometer) is a stratospheric balloon experiment designed to detect low-energy cosmic ray antinuclei (< 0.25 GeV) as an indirect signature of dark matter. The experiment exploits an innovative particle identification approach based on the formation of an excited atom and its consequent de-excitation and decay. GAPS will provide unprecedented sensitivity to cosmic antideuterons, an antiproton spectrum in a hitherto unexplored energy range and high sensitivity to cosmic antihelium. The first flight is foreseen to take place from the McMurdo Station in Antarctica during the austral summer of 2024. The instrument is currently undergoing integration and calibration in anticipation of launch. In this paper, the latest tracker electronics energy threshold calibration results will be presented.